GEOGRAPHY OF ASCARIASIS IN BELARUS: SOCIOCULTURAL AND ANTHROPOLOGICAL ISSUES (Part 1) - S. V. Kandrychyn (Российский паразитологический журнал, 2016)
Objective of research: The analysis of spatial distribution of ascariasis among the population in different regions of therepublic ofBelarus with respect to anthropological and cultural aspects. Investigations for regional differences in ascariasis conducted in theUSSR were focused rather on climatic, hygienic and economic factors and didn’t consider the causative role of cultural and anthropological factors in epidemiological process. The study is aimed at correlation of regional indices of ascariasis with the previously defined spatial historical gradient manifested inBelarus.Materials and methods: The effect of social and cultural spatial gradient was assessed by comparison of difference in ascariasis morbidity between eastern and western regions ofBelarus. Thus, the effect of ethnic and anthropological spatial gradient was considered in comparison of epidemiological indices between theBrest region (south-western part ofBelarus) andVitebsk region (north-eastern part). The analysis was conducted with the historical perspective; the regional epidemiological statistics were provided for two periods 1970-1989 and 2000-2014. Regional statistical materials of therepublic ofBelarus presented in the annual reports of the national Ministry of Health were used as an empirical basis.Results and discussion: The analysis showed, that the differentiation trend in distribution of ascariasis inBelarus correlates both with historical-cultural and anthropological spatial gradients. The identified pattern of regional differentiation allows to evaluate the complex effect of sociocultural and anthropogenic components on epidemiological features of ascariasis.